Heaven, Hell, and Everything in Between: Murals of the Colonial Andes - Cohen Suarez, Ananda (Recovering Languages and Literacies of the Americas, 2016)
Examining the vivid, often apocalyptic church murals of Peru from the early colonial period through the nineteenth century, Heaven, Hell, and Everything in Between explores the sociopolitical situation represented by the artists who generated these murals for rural parishes. Arguing that the murals were embedded in complex networks of trade, commerce, and the exchange of ideas between the Andes and Europe, Ananda Cohen Suarez also considers the ways in which artists and viewers worked through difficult questions of envisioning sacredness.This study brings to light the fact that, unlike the murals of New Spain, the murals of the Andes possess few direct visual connections to a pre-Columbian painting tradition; the Incas' preference for abstracted motifs created a problem for visually translating Catholic doctrine to indigenous congregations, as the Spaniards were unable to read Inca visual culture. Nevertheless, as Cohen Suarez demonstrates, colonial murals of the Andes can be seen as a reformulation of a long-standing artistic practice of adorning architectural spaces with images that command power and contemplation. Drawing on extensive secondary and archival sources, including account books from the churches, as well as on colonial Spanish texts, Cohen Suarez urges us to see the murals not merely as decoration or as tools of missionaries but as visual archives of the complex negotiations among empire, communities, and individuals.